The selection of construction project manager by using analytical hierarchy process (AHP) - Lau, Hui Seng (2006)
The scope of this research deals with the decision making process concerning selection of the finalists for position of project manager. The Analytical Hierarchy Process (AHP) and the Decision Support Software program-Expert Choice was used to assist with the decision. The research focus on the integration of Analytical Hierarchy Process (AHP) and Decision Support Software-Expert Choice into overall decision making process. The first objective of this research is to identify procedure in selection of a project manager. The second objective is to identify the factor and criterions that should be considered in selection process. Finally, a new framework as a Decision Support System (DSS) for evaluating project manager called Project Manager Selection System (PMSS) will be developed based on AHP. The research method used includes the knowledge acquisition technique, data analysis, and model development process. The study will focus on 100 local construction companies to capture the knowledge from the expert on the selection process. It is believe that the proposed framework will provide an even more structured approach and assist in formulating guidelines for construction company in selection of a project manager.